Reforming the rape offence in Norwegian criminal law - Jacobsen, Jørn (Bergen journal of criminal law & criminal justice, 2020)
This article addresses the content, context and development of the Norwegian rape offence to frame and explain current reform discussions. The authors describe how the offence has gradually expanded over time by partial reforms, the last in 2000, leading up to the contemporary stand of law. The article shows that the role and priorities of the feminist movement has had consequences for how the rape offence has developed. There are currently debates on whether to further revise the rape offence. While debaters share the view that rape is a serious offence and that more should be done to combat it, they are divided in how they see the potential and role of law; some debaters emphasise law as a practical instrument, others instead focus more on its symbolic functions. The authors argue that both perspectives are legitimate and needed, and see this acknowledgment as key for moving debates forward.